Analysis of Small Scale Topography and Local Precipitation in Bangka Belitung Island: Ratih Prasetya, Rizki Adzani - Ratih Prasetya Ratih Prasetya; Rizki Adzani Rizki Adzani (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2020)
Weather early warning forecast has been developed using various method and data to investigate small scale weather characteristic. Each region, especially in low latitude has unique and dynamic local weather circulation. Bangka Belitung Island has a typical topography consists of hilly region and directly adjacent to the sea. Thus, this expected to have a high impact in local weather circulation. The used of in-situ data (air temperature, rainfall amount also wind surface speed and direction), weather satellite observation and meteorological model is chosen to investigates the local weather circulation characteristic. Findings in this study is that topography, has influencing and controlling local circulation such as the presence of land breeze and sea breeze supporting the formation of convective clouds around the hills in Bangka Belitung Island. Wind surface analysis shows that strong sea breeze activity occurred during the MAM period. Himawari satellite imagery analysis showed that rain occurred in the afternoon and only occurred in the mainland region of Bangka Belitung.